2009
DOI: 10.1021/es8024098
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Hydraulic Tomography Surveys for Predicting Flow and Transport in Heterogeneous Aquifers

Abstract: This study shows how a cost-effective hydraulic tomography survey (HTS) and the associated data estimator can be used to characterize flow and transport in heterogeneous aquifers. The HTS is an improved field hydraulic test that accounts for responses of hydraulic stresses caused by pumping or injection events at different locations of an aquifer. A sequential data assimilation method based on a cokriging algorithm is then used to map the aquifer hydraulic conductivity (K). This study uses a synthetic two-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…All these studies have consistently shown that transient HT can identify not only the pattern of the heterogeneous hydraulic conductivity field but also the variation of specific storage. More importantly, the hydraulic property fields estimated by HT have been demonstrated to yield much better predictions of flow and transport processes than conventional characterization approaches [see Yeh and Zhu, 2007;Ni et al, 2009;Huang et al, 2011;Illman et al, 2012]. Recent work by Berg and Illman [2011b] further substantiated the robustness of HT for a highly heterogeneous geological medium with a variance of log hydraulic conductivity of 5.4 and a vertical correlation scale of 0.15 m. Thus, the call for changing the way we collect and analyze data for characterization of aquifers by Yeh and Lee [2007] appears to be well founded.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies have consistently shown that transient HT can identify not only the pattern of the heterogeneous hydraulic conductivity field but also the variation of specific storage. More importantly, the hydraulic property fields estimated by HT have been demonstrated to yield much better predictions of flow and transport processes than conventional characterization approaches [see Yeh and Zhu, 2007;Ni et al, 2009;Huang et al, 2011;Illman et al, 2012]. Recent work by Berg and Illman [2011b] further substantiated the robustness of HT for a highly heterogeneous geological medium with a variance of log hydraulic conductivity of 5.4 and a vertical correlation scale of 0.15 m. Thus, the call for changing the way we collect and analyze data for characterization of aquifers by Yeh and Lee [2007] appears to be well founded.…”
Section: Introductionmentioning
confidence: 99%
“…However, as pointed out in the theoretical study by Ni et al . [], even if a homogenous model can provide an appropriate fit, it will not capture the scale‐dependent increase of dispersion with transport distance [see, e.g., Molina‐Giraldo et al ., ; Gelhar et al ., ]. In contrast, by reconstructing transport‐relevant structures, their effect on macrodispersion is explicitly simulated, and thus the heterogeneous model is more suited for predicting solute transport along shorter or longer distances.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Ni et al . [], we also compare the BTC prediction by reconstructed model to that of a homogenous one.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the flow simulation, the depth-averaged conservative solute transport equation for saturated fractured porous media is governed by the ADE and can be written as (e.g., Dagan, 1989;Ni et al, 2009;Zheng and Bennett, 2002): 25…”
Section: Flow and Transport Equationsmentioning
confidence: 99%